High-Protein Foods and Physical Activity Protect Against Age-Related Muscle Loss and Functional Decline. (25th May 2017) - Bradlee, M Loring; Mustafa, Jabed; Singer, Martha R; Moore, Lynn L
Abstract: Background: Some clinical trials suggest that protein supplementation enhances the effects of resistance exercise on skeletal muscle mass (SMM); fewer studies examine the effects of diets rich in protein-source foods on SMM and functional status among community-dwelling adults. Methods: Data from the Framingham Offspring study including diet (three-day records, exams 3 and 5), physical activity (exams 2 and 4), percent SMM (%SMM) (exams 6 and 7), and functional performance (exams 5 through 8) were used to evaluate independent and combined effects of physical activity and high-protein foods on adjusted mean %SMM (using analysis of covariance) and risk of functional decline (using Cox proportional hazard's models). Analyses were adjusted for such factors as age, education, height, smoking, and fruit and grain consumption). Results: Higher intakes of protein-source foods (red meat, poultry, fish, dairy, and soy, nuts, seeds and legumes) were associated with higher %SMM over 9 years, particularly among women. Men and women with higher intakes of foods from animal sources had a higher % SMM regardless of activity; beneficial effects of plant-based protein foods were only evident in physically active adults. Active subjects with higher intakes of animal or plant protein-source foods had 35% lowest risks of functional decline. Among less active individuals, only those consuming more animal protein-source foods had reduced risks of functional decline (HR: 0.7l; 95% CI: 0.50–1.01). Conclusion: Higher intake of animal-protein foods, alone and especially in combination with a physically active lifestyle, was associated with preservation of muscle mass and functional performance in older adults.